Digital marketing all-in-one for dummies - Diamond, Stephanie (--For dummies., 2019)
Unlock the value in online marketing A well-executed digital marketing plan is a proven component of success in business, and Digital Marketing All-In-One For Dummies covers everything you need to build and implement a winning plan. Whether you're a novice in the online space or an expert marketer looking to improve your digital ROI, this book has easy-to-absorb tips and insights that will turn online prospects into loyal customers. This book compresses the essential information on 8 topics, so you have all the information you need and none of what you don't. You'll learn social media marketing, marketing to millennials, account-based marketing, influencer marketing, content marketing strategies, and more! -Use targeted, measurable marketing strategies to promote brands and products -Increase brand awareness, customer acquisitions, and audience engagement -Measure what your online traffic is worth and improve ROI on digital marketing -Develop a solid digital marketing plan and put it to work for your brand From SEO and SEM to brand awareness and why you need it, Digital Marketing All-In-One For Dummies will help you level up your digital marketing game and avoid the common mistakes that might be holding your business back.